Behavioral sleep medicine—The need for harmonization of clinical best practice outcome measures in children and adolescents with intellectual or developmental disabilities and restless sleep - Silvestri, Rosalia; Ipsiroglu, Osman S. (Frontiers in Psychiatry, 2022)
In behavioral medicine, sleep disorders may be considered comorbidities and precipitating factors to intellectual or developmental disabilities (IDD). Nevertheless, sleep alterations have often been neglected in favor of daytime features and symptoms, albeit simple behavioral nighttime observations may disclose hypermotor features that characterize restless sleep. These features are linked to central iron deficiency which is often exacerbated by vitamin D deficiency, interfering with both dopaminergic and serotonergic mechanisms, thus creating an imbalance affecting daytime behavior and mood. Several sleep-related motor disorders such as bruxism, periodic and aperiodic leg movements, Restless Legs Syndrome (RLS), and Restless Sleep Disorder (RSD) are commonly seen in Attention Deficit Hyperactivity Disorder (ADHD) and Autism Spectrum Disorders (ASD). However, they are rarely diagnosed in affected children and adolescents. Hence, they aren't therapeutically addressed and their symptoms may be worsened by the side-effects of drugs used to contain disruptive daytime behavior, such as antipsychotics and antidepressants. In children with IDDs, obesity, inactivity and metabolic effects of antipsychotics often lead to Sleep Disordered Breathing (SDB), an inflammatory state leading to “hyperactive” lethargy and hypoxic chain and vitamin D alterations. Simple routine blood tests may favorably complement caregiver observations and ambulatory sleep recordings, leading to a sleep disorder diagnosis and consequent therapy. Treating SDB, RLS, and RSD favorably impacts vigilance, behavior, social competence, and academic skills in healthy and IDD children. Thus, considering the root causes of functional and categorical diagnoses within a clinical framework may engender a more precise diagnosis, benefitting daytime and nighttime management of hyperactive behaviors.